Lipid profile pattern in chronic viral hepatitis C in Makurdi, Nigeria - Ayu Agbecha; Chinyere Adanna Usoro; Maisie Henrietta Etukudo (Wolters Kluwer Medknow Publications, 2017)
Context: Hepatitis C virus (HCV) infection with a worldwide distribution causes liver disease. The liver is the principal site for formation and clearance of lipoproteins. Aim: The purpose of this study is to assess the influence of HCV on lipid metabolism and the effect of the stages of this disease on lipid pattern in infected patients. Materials and Methods: The study involved the selection of 36 chronic hepatitis C (CHC) patients attending the clinic at a tertiary hospital in Makurdi, Nigeria. After fulfilling the inclusion criteria, 36 anthropometrically matched apparently healthy individuals were selected as a control to the CHC group. CHC is defined as patients, who continuously tested positive for anti-HCV antibody for up to 1 year during their periodic visit to the clinic. Results: There was no significant (P > 0.05) difference between the mean systolic blood pressure (BP), diastolic BP, age, waist circumference, body mass index of chronic HCV, (CHCV) and controls. There was a significantly lowered total cholesterol (P = 0.029) and high-density lipoprotein cholesterol (HDL-C) (P = 0.000) in CHCV patients compared to the matched controls. There was a significantly lowered total cholesterol (P = 0.004) and HDL-C (P = 0.000) in asymptomatic CHC compared to the matched controls. Conclusion: Lipid profile monitoring may help in the diagnosis of hepatic infection severity and may also act as a good prognostic sign, so it must be analyzed in all advanced hepatic infection cases.